Ok so let’s do .48/3 then divide 3.84 by our answer to get 24
Answer:
Step-by-step explanation:
bruh
Answer: The attachment is blank
Step-by-step explanation: :/
Answer:
step back u idiot
Step-by-step explanation:
Answer:
(a) h(x) = 1/2x -1/2
Step-by-step explanation:
The inverse of the function y = f(x) is found by solving x = f(y).
__
<h3>setup</h3>
x = f(y)
x = 2y +1 . . . . . . use the definition of f(x)
<h3>solution</h3>
x -1 = 2y . . . . . subtract 1
(x -1)/2 = y . . . . divide by 2
y = 1/2x -1/2 . . . . eliminate parentheses
h(x) = 1/2x -1/2 . . . write in functional form
The inverse of f(x) = 2x+1 is ...
h(x) = 1/2x -1/2